GRP-072 Exposure to Antineoplastic Agents in Oncology Departments: Practise Survey and Information to the Personnel of Three Oncology Departments. (12th March 2013) - Slimano, F; Mourad, MC; Mestier, L De; Regouby, C; Bouche, O
Abstract : Background: The exposure of pharmacy technicians to antineoplastic agents (AAs) has been widely studied, but less is known about risks of exposure and awareness of nurses, nursing auxiliaries and cleaning personnel. Purpose: To evaluate the practise and the awareness of oncology nurses (ONs), nursing auxiliaries (NAs) and cleaning personnel (CP) concerning exposure to AA. Materials and Methods: Three questionnaires were distributed to ONs, NAs and CP in three oncology wards including one paediatric ward. Participants were asked 10, 11 and 12 questions respectively about their practises and awareness of exposure to AAs. Results: For ONs (n = 38), gloves are more often worn when manipulating syringes than when manipulating infusion bags (60.5% vs. 36.8%, p < 0.05). 26.3% considered themselves well informed but 97.4% thought information could be improved. 81.6% of ONs suspected that AAs had teratogenic effects and 10.5% of them thought that AAs did not have mid- or long-term toxic effects. For NAs (n = 14), wearing gloves while washing patients or eliminating excreta was more frequent than mask wearing (64.3% vs. 5.3%). 28.6% considered themselves well informed but 92.9% thought information could be improved. 85.7% of NAs suspected that AAs had teratogenic effects and 14.3% of them thought that AAs did not have mid- or long-term toxic effects. For CP (n = 10), 62.5% wore gloves for bed making and 80.0% for sanitation cleaning. All of them considered themselves not sufficiently informed and 90.0% thought that AAs had teratogenic effects whereas 10% of them thought that AAs did not have mid- or long-term toxic effects. All (n = 62) reported routine use of water and soap (46.8%) or hydro-alcoholic solution (25.8%) after a potential exposure to AAs. Conclusions: Lack of information suggested the necessity of informing the nursing and cleaning personnel on the oncology ward in some fields. A teaching session was arranged by department. No conflict of interest.